The Routledge handbook of urban logistics - Monios, Jason; Budd, Lucy; Ison, Stephen (Abingdon, Oxon ; New York, NY : Routledge, 2023)
"The Routledge Handbook of Urban Logistics offers a state of the art, comprehensive overview of the discipline of urban and city logistics. The COVID-19 pandemic and the rise in internet shopping in particular has placed new demands on urban logistics which require innovative technological and policy responses. Similarly, the necessity for sustainable urban logistics offers both a challenge and opportunity for development and seeks to address traffic congestion, local air quality, traffic related degradation, the use of energy, safety aspects and noise. Featuring contributions from world-leading, international scholars, the chapters examine concepts, issues and ideas across six topic areas that reflect the increasingly diverse nature of current research and thinking in urban logistics: key features of urban logistics, freight transport, sectors in urban logistics, technical aspects, policy, and environmental and social sustainability. Each chapter provides an overview of current knowledge, identifies issues, discusses the relevant debates in urban logistics and the future research agenda. This handbook offers a single repository on the current state of knowledge, written from a practical perspective, utilising theory that is applied and developed using real-work examples. It is an essential reference for researchers, academics and students working in all areas of urban logistics, from policy and planning to technology and sustainability, in addition to industry practitioners looking to develop their professional knowledge"--
Keywords: City planning; COVID-19 Pandemic, 2020- -- Economic aspects; Telemarketing; Urban transportation; BUSINESS & ECONOMICS / General; BUSINESS & ECONOMICS / Urban & Regional; BUSINESS & ECONOMICS / Industries / Transportation